Highly efficient preparation of ZnO nanorods decorated reduced graphene oxide nanocomposites - Abdul Rahman, Marlinda; Huang, Nay Ming; Muhamad, Muhamad Rasat; Mohamed Noor, An'amt; Chang, Betty Yea Sze; Yusoff, Norazriena; Harrison, Ian; Lim, Hong Ngee; Kumar, S. Vijay (Elsevier, 2012)
A one-step method for the synthesis of zinc oxide/reduced graphene oxide (ZnO/rGO) nanocomposites by a hydrothermal technique is reported. This simple method involves a hydrothermal treatment of a solution comprising graphene oxide (GO), Zn(CH3COO)2.2H2O, NaOH and NH3.H2O. The concentration of GO as a starting material plays an important role in the density distribution of ZnO nanorods on the rGO sheets and on the percentage of the formation of ZnO/rGO nanocomposites. The resulting rod-like ZnO nanoparticles formed on the rGO sheets, in high density, has a potential in the gas sensing application.